2011
DOI: 10.1902/jop.2010.100339
|View full text |Cite
|
Sign up to set email alerts
|

Implant Stability and Peri‐Implant Parameters in Free Vascularized Iliac Graft Transplantation Patients: Report of Three Ameloblastoma Cases

Abstract: The implant-supported prosthetic rehabilitation of patients with ameloblastomas reconstructed with free vascularized iliac crest grafts can be a predictive alternative for improving the quality of life of patients in which a high implant stability and acceptable peri-implant health may be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In 3 cases, restoration of missing teeth was achieved by secondary dental implant placement in the bone grafts and by using implant-supported prostheses. Previous studies have demonstrated the advantages of implant placement and subsequent restoration with prostheses for the rehabilitation of oral competence, mastication, speech and facial contour in patients with mandibular defects (25,29,30). …”
Section: Discussionmentioning
confidence: 99%
“…In 3 cases, restoration of missing teeth was achieved by secondary dental implant placement in the bone grafts and by using implant-supported prostheses. Previous studies have demonstrated the advantages of implant placement and subsequent restoration with prostheses for the rehabilitation of oral competence, mastication, speech and facial contour in patients with mandibular defects (25,29,30). …”
Section: Discussionmentioning
confidence: 99%
“…Most articles were published after 2013 (25: 71.4%). Four (24%) studies were conducted in India [ 42 , 44 , 55 , 58 ], Turkey [ 27 , 32 , 47 , 49 ] and Brazil [ 37 , 46 , 52 ], 3 (18%) in the USA [ 30 , 35 , 41 ], Spain [ 31 , 50 , 57 ], China [ 28 , 33 , 43 ], Korea [ 38 , 39 , 53 ], 2 (12%) in Italy [ 36 , 48 ], Finland [ 29 , 40 ] and other studies (6%) in Japan [ 54 ], Colombia [ 59 ], Iran [ 56 ], Taiwan [ 25 ], Austria [ 26 ] and Romania [ 45 ] (Tables 2 and 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 (19%) cases were reported as recurrent AM, which were reintervened. It was also observed that 94% of patients had conventional/multicystic AM [ 25 , 27 30 , 32 49 , 51 59 ], and only 4 (6%) cases were diagnosed as unicystic type AM [ 26 , 31 , 42 , 50 ]. The most common histologic variant was the plexiform type (11%) [ 26 , 37 , 39 , 49 ], followed by the follicular variant (8%) [ 26 , 34 , 38 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Ameloblastoma is a benign but locally aggressive odontogenic tumor that accounts for 1% of all oral tumors and for 9 to 11% of all odontogenic tumors. Among these factors, orofacial tumors should be highlighted, and ameloblastoma is 1 of the most common tumors associated with this pathology.…”
mentioning
confidence: 99%